Cover, Content, and Editorial Note from Borneo J Pharm Vol. 7 No. 1 February 2024 - Borneo J Pharm, Chief Editor of (Borneo Journal of Pharmacy, 2024)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of the Borneo Journal of Pharmacy (Borneo J Pharm) was published in February 2024. This edition contains ten articles: Pharmacognosy-Phytochemistry, Analytical Pharmacy-Medicinal Chemistry, and Clinical-Community Pharmacy. This edition includes writings from four countries: India, Indonesia, South Africa, and Thailand. The authors come from several institutions, including Universitas Muhammadiyah Kalimantan Timur, Universitas Gadjah Mada, Khon Kaen University, Universitas Muhammadiyah Surakarta, University of the Witwatersrand, Universitas Sanata Dharma, Universitas Halu Oleo, Universitas Bhakti Kencana, Universitas Negeri Gorontalo, Sekolah Tinggi Farmasi Mahaganesha, Universitas Tanjungpura, National Research and Innovation Agency of the Republic of Indonesia, Universitas Surabaya, Universitas Airlangga, Universitas Indonesia, M. S. Ramaiah University of Applied Sciences, and Universitas Muhammadiyah Yogyakarta. Editorial boards are fully aware that this edition has room for improvement. Hence, with all humility, we are willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors, reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope all parties, especially the contributors, can re-participate in the publication in the next edition in May 2024. Wassalamu’alaikum Wr. Wb.